Analisis Anteseden Kewirausahaan Di Perusahaan Keluarga - Ariyani Wahyu Wijayanti; Salman Faris Insani (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2016)
This research examines and analyzes the corporate entrepreneurship antecedent in family firms; the willingness to change, generation involvement, perceived technological opportunity, and strategic planning. The samples of this research are family firms which located in the center of batik industry in Surakarta, Sukoharjo, and Sragen. Eighty two respondents in this study are business owners or respective family members who are involved in managing the organization and able to disclose required information for this research. The research used non-probability sampling and purposive sampling as the method and technique. By using multiple regression analysis, the findings have shown that corporate entrepreneurship antecedent is a willingness to change and strategic planning, while generation involvement and perceived technological opportunity do not influence on corporate entrepreneurship.